Analisis Biaya Produksi di UD. Berkat Jaya Mandiri Desa Simpang Jernih Kecamatan Simpang Jernih - Muhammad; Dewi Rosa Indah (Fakultas Ekonomi Universitas Samudra, 2020)
The purpose of this study is to analyze the production costs at UD. Blessed Jaya Mandiri Simpang Jernih Village, Simpang Jernih Subdistrict. The data used in this study are production cost data for 2014-2016. The data analysis method shows that the total production costs in 2014 amounted to IDR 507,200,000 with a total production of 268 units and a cost per unit of IDR 1,892,537. In 2015, the highest total production costs reached IDR 535,900,000 with a total production of 283 units and a cost of goods per unit IDR 508,100,000 with a total production of 254 units and a cost of goods per unit of IDR 2,000,393. in 2015, which amounted to IDR 1,893,639 due to an increase in the total production cost to IDR 535,900,000 and a total production of 283 units.